The clinical effectiveness and cost-effectiveness of primary human papillomavirus cervical screening in England : extended follow-up of the ARTISTIC randomised trial cohort through three screening rounds /: extended follow-up of the ARTISTIC randomised trial cohort through three screening rounds. (April 2014) - Kitchener, Henry C
No abstract available